Seychelles : Staff Report for the 2015 Article IV Consultation, Second Review Under the Extended Arrangement, and Request for Waiver and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2015)
Context: The robust recovery from the 2008 balance of payments and debt crisis has resulted in improved economic and social outcomes. Continued policy discipline and reforms are needed for the microstate to mitigate its geographical and population constraints and maintain momentum in developing a diversified and resilient economy. Focus: With the fiscal stance anchored by the authorities' debt reduction objective, macroeconomic discussions concentrated on the smooth functioning of monetary and exchange rate policies. On the structural agenda, the dialogue focused on policies to promote sustained and inclusive growth, particularly on the appropriate role for state-owned enterprises (SOEs). Review: The program is on track. The authorities met the end-December quantitative performance criteria except for narrowly exceeding the ceiling on reserve money. The structural agenda remains broadly on track despite some delays. Staff recommends completion of the second review under the Extended Arrangement and modification of the performance criteria for end-June and end-December 2015, and supports the authorities' request for a waiver for the end-December 2014 performance criterion for reserve money. Outlook and risks: With the external position having stabilized since the last review, fundamentals are strengthening. However, the economy remains highly vulnerable to global developments, including weakness in the key European markets, while domestic risks center on the role of the SOEs. Recommendations: The authorities' objective of reducing public debt below 50 percent of GDP by 2018 remains an appropriate and attainable anchor for fiscal policy. The monetary policy framework should be further enhanced by increasing its forward orientation in the context of a flexible exchange rate. Structural measures should focus on fostering inclusiveness and private sector-led growth, while improving economic governance and the focus of SOEs. Data: Data provision is broadly adequate for surveillance. Priority areas include improved GDP statistics, strengthening external sector statistics, and extending coverage of the international investment position.